Delayed Lactogenesis Is Associated with Suboptimal Breastfeeding Practices: A Prospective Cohort Study. Issue 4 (25th December 2019) - Huang, Li; Xu, Shangzhi; Chen, Xi; Li, Qian; Lin, Lixia; Zhang, Yu; Gao, Duan; Wang, Huanzhuo; Hong, Miao; Yang, Xuefeng; Hao, Liping; Yang, Nianhong
ABSTRACT: Background: Breastfeeding has many established health benefits to both babies and mothers. There is limited evidence on the association between delayed lactogenesis and breastfeeding practices. Objective: We assessed the association between delayed lactogenesis and breastfeeding practices in women initiating breastfeeding. Design: We used data from a prospective cohort study in Wuhan, China, which enrolled pregnant women at 8– 16 weeks of gestation and followed up to postpartum. Women were included who had a singleton live birth, initiated breastfeeding, and provided information on infant feeding. Maternal lactogenesis status was assessed by face-to-face interview at day 4 postpartum. Breastfeeding practices (full breastfeeding and/or any breastfeeding) were queried by telephone interview at 3, 6, and 12 mo postpartum. Poisson regression and Cox regression were used to identify the association between delayed lactogenesis and breastfeeding practices. Results: Delayed lactogenesis was reported by 17.9% of the 2877 participants. After adjusting for potential confounders, when compared with timely lactogenesis, delayed lactogenesis was significantly associated with higher risk of inability to sustain full breastfeeding at 3 mo postpartum (RR: 1.24, 95% CI: 1.10, 1.39) and 6 mo postpartum (RR: 1.14, 95% CI: 1.04, 1.24). Delayed lactogenesis was also significantly associated with early termination of any breastfeeding (HR: 1.15, 95% CI: 1.01, 1.30) in the adjusted model. In a combined analysis, women with higher gestational weight gain (GWG, ≥16 kg for underweight and normal weight, 15 kg for overweight/obesity) and who subsequently experienced delayed lactogenesis had the highest risk of ending any breastfeeding earlier (adjusted HR: 1.32, 95% CI: 1.11, 1.55) compared with those who gained less GWG and experienced timely lactogenesis. Conclusions: This study shows that delayed lactogenesis was associated with low rate of full breastfeeding and shorter duration of any breastfeeding. Greater efforts to promote breastfeeding should be targeted towards women with delayed lactogenesis.